Measuring the Possibility of Middle Ear Discharge for COVID-19 Test Material - Kadriyan, Hamsu; Rizkika Abtartu, Lalu Hizrian; Wardoyo, Eustachius Hagni; Andiwijaya, Fahrin Ramadan (Interdisciplinary Perspectives on Infectious Diseases, 2022)
The COVID-19 pandemic is still ongoing, and new variants continue to emerge. Various examination methods and sampling specimens are continuously being developed and published. The standard for sampling is in the nasopharynx. However, in children, this is often uncomfortable and at risk of eliciting complications. Therefore, it is necessary to look for other alternative sampling sites such as fluid from the middle ear. Scientific evidence shows that the middle ear can be a place for the attachment and growth of the SARS-CoV-2 virus. Currently, to the best of the author's knowledge, there have been no publications on middle ear discharge as a sample for the determination of the diagnosis of COVID-19. Based on this, the authors would like to explore the possibility of middle ear discharge for COVID-19 test material. A narrative review on the use of middle ear discharge as a potential diagnostic specimen for COVID-19 was conducted. The searches were conducted in the PubMed and ProQuest databases.